Debate: "How low should LDL cholesterol be lowered for optimum prevention of vascular disease?" Viewpoint: "Below 100 mg/dl" - Brown, W Virgil (BioMed Central, 2001)
Arteriosclerotic vascular disease manifests as heart disease, stroke, aortic aneurysms, and peripheral vascular disease, and is a growing problem world-wide. The preventive efforts made so far have demonstrated that lowering LDL-C is one action that individuals and populations can do with significant success in delaying the onset of clinical events. Epidemiological studies and small clinical trials suggest that more aggressive and sustained lowering to LDL-C below 100 mg/dl could result in 50 to 70% reductions in vascular death. The full benefit of reducing LDL-C is only now being tested in adequate clinical trials.